2004
DOI: 10.1097/00054725-200409000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Fibrosis in Experimental Colitis by Captopril: the Role of tgf-β1

Abstract: These data demonstrate for the first time that the prophylactic administration of captopril is effective in preventing colonic fibrosis in TNBS-induced colitis. The antifibrotic action of captopril could be due to the blockade of TGFbeta-1 overexpression, and/or to a direct down-regulation of TGFbeta-1 transcript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 69 publications
3
98
0
1
Order By: Relevance
“…It is important to note that our findings are supported by other investigators who have recently identified a potential benefit in blocking the renninangiotensin (RAS) pathway in inflammatory bowel disease. Wengrower, et al showed that fibrotic changes were significantly diminished in a trinitrobenzene sulphonic acid (TNBS) induced model of colitis in rats (56). Blockade of the RAS pathway using angiotensinogenknock out mice also resulted in a diminution of the level of inflammation in this TNBS model (57).…”
Section: Discussionmentioning
confidence: 96%
“…It is important to note that our findings are supported by other investigators who have recently identified a potential benefit in blocking the renninangiotensin (RAS) pathway in inflammatory bowel disease. Wengrower, et al showed that fibrotic changes were significantly diminished in a trinitrobenzene sulphonic acid (TNBS) induced model of colitis in rats (56). Blockade of the RAS pathway using angiotensinogenknock out mice also resulted in a diminution of the level of inflammation in this TNBS model (57).…”
Section: Discussionmentioning
confidence: 96%
“…ACE inhibitors have had mixed results in animal models of colitis. Wengrower et al, demonstrated that prophylactic administration of Captopril in TNBS colitis could reduce damages scores and fibrosis after 21 days, as well as the levels of Ang II and TGF-beta [13]. On the other hand treatment with the same inhibitor administered after the induction of acute colitis did not show significant benefits in the observed lesions at the dose tested [45].…”
Section: Discussionmentioning
confidence: 99%
“…This led us to hypothesize that the inhibition of Ang II could attenuate the inflammation and subsequent damage found in acute colitis. Recently it was demonstrated that an ACE inhibitor, Captopril, could reduce the levels of Ang II and the colonic fibrosis found in an animal model of colitis [13]. Moreover, losartan, an Ang II type I receptor blocker was found to have beneficial effects in colitic mice confirming the involvement of this receptor [14].…”
Section: Introductionmentioning
confidence: 94%
“…These drugs have been shown to produce a number of beneficial antiinflammatory effects in rodent models of intestinal inflammation. [48][49][50][51][52][53] Though originally thought to exert their action predominantly via blockade of the effects of Ang II, recent evidence suggests some of the beneficial effects may be through upregulation of the alternative RAS with increased tissue Ang (1-7). [54][55][56] Hence, if translated to human trials in IBD, these inexpensive, readily available medications may be suitable for treatment of inflammation and fibrosis in IBD.…”
Section: (0-11)mentioning
confidence: 99%